Improving primary literacy linking home and school - Feiler, Anthony (London Routledge, 2007)
"With a focus on improving children's literacy skills, this book provides practical answers to key questions that are directly relevant to all primary teachers and to many parents. It presents new ways of linking learning in home and school through a range of activities that can be used to share knowledge between children, parents and teachers."--Publisher's description.
Why link home and school learning? -- Literacy at home -- Literacy at school -- Literacy activities that take school to home -- Literacy activities that bring home into school -- Home-school knowledge exchange : benefits and challenges.
Keywords: Language arts (Elementary) -- United States; Education, Elementary -- Parent participation -- United States; Home and school -- United States